Novel squalene-producing thraustochytrids found in mangrove water. Issue 10 (3rd October 2017) - Otagiri, Masato; Khalid, Ammara; Moriya, Shigeharu; Osada, Hiroyuki; Takahashi, Shunji
Abstract: On extended screening of squalene-producing strains in Okinawa mangrove water, we identified 14 novel squalene-producing thraustochytrids from 172 unialgal clonal isolates. The novel thraustochytrids produced 13.9–7.54 mg squalene/g dry cell weight. Eight isolates were found to belong to potentially novel squalene-producing genera, forming a monophyletic cluster independent from any known thraustochytrids.